Banking Competition Measurement and Banking Sector Performance: Analysis of 4 ASEAN Countries - Buddi Wibowo (Signifikan: Jurnal Ilmu Ekonomi, 2017)
Many believe concentrated  banking industry which is dominated by few  big banks creates lower  competition, high profitability, and low efficiency. The main issue in empirical testing of this hypothesis is how to measure banking competition level. Traditional measures of competition are  concentration ratio and Herfindahl-Hirschman Index. This study uses three measures of banking level competition which are widely used in recent  financial literature: Boone Indicator, Lerner Index and H-Panzar-Rosse  statistics.  Lerner Index and H-Panzar-Rosse statistics resulted a similar competition level conclusion, while Boone Indicator produced slightly different output. Industry concentration produced opposing results with those three level of industry competition measurement methods. The results show  banking competition tend to be a monopolistic competition in ASEAN countries, especially in Indonesia which banks’ strategy basically were non-pricing strategy. Competition significantly caused lower profitability, while banking efficiency was not significantly affected by level of competition.DOI:  10.15408/sjie.v6i1.4547